The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.molonc.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered mouse models of PI3K signaling in breast cancer

Abstract: Breast cancer is the most common type of cancer in women. A substantial fraction of breast cancers have acquired mutations that lead to activation of the phosphoinositide 3-kinase (PI3K) signaling pathway, which plays a central role in cellular processes that are essential in cancer, such as cell survival, growth, division and motility. Oncogenic mutations in the PI3K pathway generally involve either activating mutation of the gene encoding PI3K (PIK3CA) or AKT (AKT1), or loss or reduced expression of PTEN. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 147 publications
2
27
0
Order By: Relevance
“…Studies using mouse models have confirmed the importance of PI3K signaling in breast cancer (16). Transgenic mice that overexpress mutant PIK3CA in conjunction with HER2/neu recapitulate resistance to anti-HER2/neu therapies (17), and conditionally overexpressed mutant PIK3CA in the mammary gland gives rise to tumors at long latency that regress upon oncogene withdrawal (18).…”
mentioning
confidence: 95%
“…Studies using mouse models have confirmed the importance of PI3K signaling in breast cancer (16). Transgenic mice that overexpress mutant PIK3CA in conjunction with HER2/neu recapitulate resistance to anti-HER2/neu therapies (17), and conditionally overexpressed mutant PIK3CA in the mammary gland gives rise to tumors at long latency that regress upon oncogene withdrawal (18).…”
mentioning
confidence: 95%
“…Numerous studies have demonstrated that well over half of breast cancers have genetic changes in components of the phosphatidylinositol-3-kinase (PI3K) signaling cascade, predicted to result in pathway activation [15]. These genomic changes include amplification, mutation or activation of receptor tyrosine kinases (HER2, EGFR), mutation or amplification of the catalytic subunit ( PIK3CA ), mutation of amplification of AKT1 , or loss of inhibition, impacting the PIK3R1 regulatory subunit, or phosphatase and tensin homolog ( PTEN ) function [25]. Considerable efforts have been directed to pharmacologic targeting of aberrant PI3K pathway activity [24, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Activating ‘hotspot’ point mutations in PIK3CA are present in about 25% of invasive breast cancers, and are even further enriched in luminal-A cancers including invasive lobular carcinoma [15]. Accumulating data from a number of different studies shows that concurrent invasive and in-situ breast carcinoma (ductal carcinoma in-situ, DCIS) in the same patient frequently harbor identical PIK3CA mutations [711].…”
Section: Introductionmentioning
confidence: 99%
“…AKT1 lies downstream of Phosphoinositide-3-Kinase (PI3K) signaling. This pathway can play numerous roles in carcinogenesis (Klarenbeek, et al 2013). To explore the role of AKT1 activation in breast cancer, a genetically engineered mouse model with expression of an artificially constitutively activated form of AKT1 targeted to mammary epithelium using the MMTV promoter was generated ( MMTV-myrAkt1 mice) (Blanco-Aparicio, et al 2007) (Table 1D).…”
Section: Carcinogen Exposure Can Promote Development Of Erα+ Mammary mentioning
confidence: 99%